Memory in the Space of Language. Memory and Remembrance in Linguistic Research - Czachur, Waldemar; Wójcicka, Marta (Język(i) w czasie i przestrzeni, 2021)
The aim of the article is to offer a linguistic reflection on the linguistic character of collective memory and collective remembrance. To this end, we will present the sources of inspirations for linguistic research that lead us to findings about the essence of collective memory in the light of ethnolinguistics, genre studies or discourse linguistics. Moreover, we will reflect on the process of collective remembrance studied from the linguistic perspective, and, consequently, on the category of time and place in this process.